Arbuscular mycorrhizal fungi reduce N2O emissions from degraded residue patches - Li, Xia; He, Guang; Li, Dandan; Bei, Shuikuan; Luan, Dongdong; Sun, Xinzhan; Yang, Gaiqiang; Huo, Lijuan; Zhen, Lina; Zhao, Ruotong (Frontiers in Ecology and Evolution, 2023)
Nitrous oxide (N2O) is a potent greenhouse gas and agricultural soils represent a major anthropogenic source. Crop residues provide nutrients for plants but also act as hotspots of N2O production. The hyphae of arbuscular mycorrhizal fungi (AMF) could proliferate in the organic patches, utilize released N from the organic patch and potentially mitigate N2O emissions. However, the effect of AMF on N2O emissions in degraded residues patches and the possible microbial mechanism remains uncertain. Here, a mesocosm experiment was conducted to investigate the impact of AMF (Funneliformis mosseae) inoculation on N2O emissions, availabilities of carbon and nitrogen, extracellular enzyme activities and the abundances of key N-cycling genes in degraded residue patches. Our results showed that AMF hyphae significantly reduced N2O emissions from degraded residuepatches. Quantitative PCR analysis of key functional genes involved in N2O production (amoA, nirK, nirS) and consumption (nosZ) showed AMF significantly reduced the abundances of bacterial amoA and nirS genes. NH4 + , NO3 -, total dissolved nitrogen (TDN), total nitrogen (TN) and dissolved organic carbon (DOC) contents decreased drastically in the presence of AMF. In addition, the activities of all tested extracellular enzymes were significantly decreased by AMF and positively correlated with DOC content. Multiple stepwise regression analysis demonstrated that the abundance of nirS gene primarily influenced N2O emissions, and was positively correlated with DOC content in degraded residue patches. Our findings indicate that AMF suppressed N2O producers, particularly nirS-type denirifiers, by slowing down the release of C and N from degraded residues, thereby leading to a cascade effect on the decrease of N2O emissions. This study provides a promising approach to mitigating N2O emissions by enhancing AMF in the agroecosystems.